Persuasive language strategies in public service advertisements: a pragmatic perspective - Pujiati, Hanip; Perdana, Muhammad Rizki; Maulana, Ade Hilman; Yunas, Lesmana Dwi Putra; Yusup, Aldian (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Public service advertisements (PSAs) play an important role in conveying social messages to shape people's behavior positively. However, the effectiveness of these messages is highly dependent on the persuasive language strategies used. This study aims to analyze persuasive language strategies in public service advertisements from a pragmatic perspective, focusing on the use of metaphors, repetitions, imperatives, and language styles that are appropriate to the social and cultural context. The method used is an explanatory literature study, which collects and analyzes data from various journal articles, books, and related research reports. Data were collected through documentation studies, then analyzed using a qualitative content analysis approach to identify patterns and main themes in persuasive language strategies. The results of the study indicate that the use of metaphors and repetitions consistently increases the emotional appeal and memory of the audience, while the use of imperatives and framing helps strengthen the urgency of the message. This pragmatic approach allows advertisements to adapt messages to the social and cultural values ​​of the community, thereby strengthening the effectiveness of communication. This study contributes to a deeper understanding of how language strategies can influence audience perceptions and behavior in the context of public service advertisements, as well as the importance of considering cultural context in designing effective messages.